Multimodal Efficacy of Health Warnings on UK Cigarette Packages: A Cognitive-Semiotic Analysis - Sadallah, Shatha H.; Halawachy, Huda (Journal of Ecohumanism, 2025)
This study investigates the impact of health warnings on cigarette packages in the UK. The common health warnings, their specific communicative functions and their effectiveness in influencing consumer behaviour and perception remain underexplored. This study aims to fill this gap by employing a qualitative multimodal social semiotic analysis to understand how textual and pictorial warnings function to communicate health-related messages effectively. The theoretical frameworks guiding this analysis are Kress's approach (2010) Multimodal Social Semiotic and Forceville’s model (2020) of Visual and Multimodal Communication. Methodologically, the study focuses on a purposive sample of seven UK cigarette packages, analysing the warnings for their semiotic effectiveness and pragmatic functions. The study reveals effective health warnings on UK cigarette packages that integrate textual, visual, and design elements. The findings also highlight the importance of cognitive relevance, showing that warnings which balance cognitive effort with substantial rewards—like emotional impact—more effectively influence behaviour change. The study suggests that more effective health warnings on cigarette packages should use a strategic integration of text, imagery, and design. It also recommends regular updates to warning designs based on ongoing audience research and enhanced public engagement in the design process to ensure that warnings remain relevant and impactful.